Realities behind their smiles economic and health condition of street vendors at Calle Real, Iloilo City - Albacete, Lariza Aklemia (Iloilo City, Philippines University of the Philippines Visayas, 2013)
Street vendor at Calle Real gather in areas where people flock and they aim to provide passer-by with commodities that are convenient and affordable. The study is designed to have better understanding of the realiities experienced by the vendor. Specifically, the study aaims to describe the current economic and health condition of the vendors at Calle Real; to identify the perceived benefits and the factors that made thee venddors stay on the business; to determine what are the health and eonomic concerns of the vendors; and to describe the percepton of street vendors regarding the policies that regulates vending at Calle Real. These objectives can be obtaained and explained with the help of quantitative descriptive research design. The researcher used the survey method to obtain information concerning the dmographics, economic and health condition of the respondents, sanitary practices and awareness of the policies set by the city government that regulates vending at Calle Real. Other methods used were participant observation, interview, transect walk and online publications. Results were analyzed using frequencies, percentages and central tendencies. Findings of the study show that most of the vendors were mostly women and majority of the vendors were between the ages 41 to 60 yeaars old. Street vending was seen as the primary source of income and most of them reported that their daialy profit is within the range of Php 251-500 for working at an average of 10.13 hours a daay. A key finding of their health condition is that many reported to have eperienced coughs, headache, fevers, stress allergy and back pains which are all symptons of sickness. Vendors are exposed to pollution, changing temperature and other uncratinties yet many claimed that they ave not acquired serious illness from selling in the streets. Most of the vendors were dissastified with the management of the government because they have cnsidered that the local governmenthad not given them any assistance. In addition, the vendors find it difficult for them to adaapt with the policies whenever there is a change in administration. For their aspirations in the next years, respondents wanted their children to finish education; to continue street vending and to have a more profitable business.
[Research Paper] (Mgt 199 : Management Research) -- Iloilo City : U.P. Visayas, 2013.